Some steps towards the development of low-cost typhoon resistant housing in the Philippines. - Boughton, Geoffrey N. (Philippine Engineering Journal)
Due to the high occurrence of typhoons in the Philippines, it is important that all housing be typhoon-resistant. Following the passage of typhoon "Heming" in the Philippines, an extensive investigation of damage to low-cost housing was undertaken. The principal aim of the activity was to isolate systematic problems in the structural action of low-cost housing and to make specific recommendations with respect to low-cost improvements to the buildings. Three problems were highlighted and appropriate recommendations have been made. An education programme will be mounted to publicize the recommendations. The paper outlines the structural damage caused by the typhoon and examines the recommendations made based on the preliminary data from the damage survey.